The moon and more - Dessen, Sarah (New York : Viking, 2013)
"During her last summer at home before leaving for college, Emaline begins a whirlwind romance with Theo, an assistant documentary filmmaker who is in town to make a movie."--
Keywords: Coming of age -- Juvenile fiction; Resorts -- Juvenile fiction; Beaches -- Juvenile fiction; Family-owned business enterprises -- Juvenile fiction; Dating (Social customs) -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Documentary films -- Production and direction -- Juvenile fiction; Love stories